2022
DOI: 10.1038/s41598-022-22484-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Potamogeton crispus harvesting on phosphorus composition of Lake Yimeng

Abstract: Harvesting is an important method used to control the overproduction of Potamogeton crispus in lakes. A three-year comparative field study was performed in a eutrophic lake (harvested area) and its connected lake (non-harvested area) to determine the effects of harvesting on the phosphorus (P) composition and environmental factors in the water and sediment. Results revealed that harvesting significantly reduced the dissolved total P and dissolved organic P (DOP) and increased the alkaline phosphatase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…After the death of submerged plants, as a result of reversible adsorption reactions, H 2 O-P re-enters a water body in the form of soluble phosphorus and is directly utilized by other aquatic organisms [12,13], while NaOH-P becomes soluble inorganic phosphorus through microbial decomposition [37,38]. This could explain the sharp increase in water phosphorus content after a decline in submerged vegetation [6,8]. Compared with H 2 O-P and NaOH-P, HCl-P is not easily dissolved or adsorbed under normal circumstances, and phosphorus is difficult for organisms to dissolve and adsorb.…”
Section: Composition and Variation In Ash Phosphorusmentioning
confidence: 99%
See 2 more Smart Citations
“…After the death of submerged plants, as a result of reversible adsorption reactions, H 2 O-P re-enters a water body in the form of soluble phosphorus and is directly utilized by other aquatic organisms [12,13], while NaOH-P becomes soluble inorganic phosphorus through microbial decomposition [37,38]. This could explain the sharp increase in water phosphorus content after a decline in submerged vegetation [6,8]. Compared with H 2 O-P and NaOH-P, HCl-P is not easily dissolved or adsorbed under normal circumstances, and phosphorus is difficult for organisms to dissolve and adsorb.…”
Section: Composition and Variation In Ash Phosphorusmentioning
confidence: 99%
“…Similarly, the variation in OP with P. crispus over time suggested that the mineralization rate differed because of differences in the rhizosphere oxygen secretion capacity of the two species, as discussed above. For the sixth week, the increase in OP might be ascribed to the abscission of linear leaves of C. demersum as the decomposition of plant residues increases the proportion of OP [6].…”
Section: Composition and Variation In Phosphorus In Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DO in the research region increases in the spring owing to P. crispus reproduction and decreases in the summer due to P. crispus decline in the water body. P. crispus growth may also absorb N and P from the River Yi, resulting in a decrease of N and P in the water [44]. N and P are released into the water during the decomposition of P. crispus, which is a major reason influencing the periodic variation in N and P concentration in the water.…”
Section: Effect Of Do On N and P Concentration In Watermentioning
confidence: 99%